THE FOREST GROWTH CYCLE IN VARIOUS FOREST TYPES - Dhanmanonda, Pricha (วารสารวนศาสตร์ไทย, 2022)
Determination of the process and rate of revegetation by using data on tree density, basal area, H* (a coefficient indicating the ideal maximum tree height) and above-ground biomass were investigated in dry dipterocarp forest (DDF), hill evergreen forest (HEF), evergreen broadleaved (EBF) and EBF (S, M and A types). The results revealed that the forest growth cycle (the gap phase, the building phase and the mature phase) were estimated to be 0-60, 60-122, 122-244 years; 0-50, 50-100, 100-200 years; 0-42, 42-70, 70-180 years for DDF, HEF and all EBF types, respectively. Rapid increase in basal area, H* and high mortality of saplings were found during the gap phase. A slow increase in basal area, H* and low mortality were found during the building phase, while the mature phase was characterized by an almost saturated basal area, H* and above-ground biomass. In the case of EBF, gap indicators flourished in the gap phase, but their dominance declined in the building phase, and finally they were excluded from the mature phase. On the other hand, evergreen oaks steadily increased their dominance as time passed. No gap species occured in the DDF and HEF.